Experimental study on the efficiency of teaching electrical engineering under conditions of blended learning - Berezenska, S. (Problems of Engineer-Pedagogical Education, 2018)
The research is grounded on a methodology developed on the basis of the "evaluation of investments in human capital" model, authored by Professor D. Kirkpatrick. The advantages of the proposed methodology include its complexity and the possibility of involving not only representatives of student and teaching staff of the institution but also potential employers in the assessment of learning outcomes. Evaluation of the teaching effectiveness is carried out in four independent stages: the definition of how many students are satisfied with the organization of educational activities in the discipline; qualitative evaluation of theoretical knowledge and practical skills acquired by students in the process of learning; research among students about the level of application of the acquired knowledge and skills in further educational activities; receiving an expert assessment of teachers and/or employers on the quality of training future specialists and satisfaction with the results of their training. In order to ensure the diversity and depth of the research, a set of diagnostic methods including questionnaires, interviewing, ranking, testing, as well as solving practical and situational tasks was proposed as the main tools of the methodology. In addition, the analysis of publications on the development of the D. Kirkpatrick's model under modern economic conditions allows us to conclude that the proposed methodology for evaluating the effectiveness of learning is appropriate to use not only to state the effectiveness of the educational process, but also as a tool for training specialists in business development planning, as well as for evaluating (diagnosing) existing problems in business.